Creating a cognitively guided instruction guidebook: the research and development of an educative curriculum for teachers - Rand, Sarah (Kansas State University, 2023)
The purpose of this study was to create an educative guidebook for teachers based on the principles of Cognitively Guided Instruction (CGI), a constructivist approach to teaching mathematics through contextual word problems. The guidebook is designed to be used as a First-Grade mathematics supplemental curriculum resource with complete, daily lessons. The development of the handbook began by identifying the problem of lack of support and professional development for teachers to enact the instructional strategies aligned with CGI. CGI is an impactful instructional method as it allows a teacher the opportunity to enact all of the National Council of Teachers of Mathematics’ “Effective Teaching Practices.” A Qualitative Content Analysis of seven of the most widely used elementary mathematics curriculum resources was conducted using a coding framework that included 11 key elements of a CGI lesson. The findings showed a strong lack of these 11 features of CGI. In some cases, they were entirely or nearly entirely absent. This data was used to inform the development of the CGI Guidebook. A first draft of five lessons was implemented by two First-Grade teachers. Revisions were made based on feedback from the teachers. The final guidebook provided First-grade teachers with a module of CGI lessons that is designed for both student and teacher learning, making it an “educative curriculum for teachers”. The “5 Practices for Orchestrating Productive Mathematics Discussions” (Smith & Stein, 2018) were also used to inform the guidebook and all 5 practices are embedded through each lesson. The guidebook provides a contextual word problem for each daily lesson, a rationale for the problem type and numbers in the problem, directions for selecting and sequencing student strategies and facilitating a discussion about the student strategies. The guidebook shows where standards are embedded in the lessons and provides, in every lesson, drawn example student strategies, rationales for the selection and sequencing of strategies as well as discussion guidance that will support the teacher to make connections between student strategies and to illuminate mathematical connections for students. The guidebook fulfills a need for access to Cognitively Guided Instruction professional development through a medium that is not currently available.
Keywords: Cognitively guided instruction; Educative curriculum materials; Self-directed learning for teachers; Curriculum design; Elementary mathematics